Hip fracture risk in patients with alcoholic cirrhosis: a population-based study using English and Danish data - Otete, Harmony E.; Deleuran, T.; Fleming, Kate M.; Card, Timothy R.; Aithal, Guruprasad P.; Jepsen, P.; West, Joe (Elsevier, 2018)
Background & aims: Cirrhosis is a risk factor for osteoporosis and fractures. However, little is known of the actual risk of hip fractures in patients with alcoholic cirrhosis. Using linked primary and secondary care data from the English and Danish nationwide registries, we quantified the hip fracture risk in two national cohorts of patients with alcoholic cirrhosis. Methods: We followed 3,706 English and 17,779 Danish patients with a diagnosis of alcoholic cirrhosis, and we identified matched controls from the general populations. We estimated hazard ratios (HR) of hip fracture for patients versus controls, adjusted for age, sex and comorbidity. Results: The 5-year hip fracture risk was raised both in England (2.9% vs 0.8% for controls) and Denmark (4.6% vs 0.9% for controls). With confounder adjustment, patients with cirrhosis had 5-fold (adjusted HR 5.5 (95% CI 4.3-6.9)), and 10-fold (adjusted HR 9.9 (95% CI 8.9-11.0)) increased rates. This association between alcoholic cirrhosis and risk of hip fracture showed significant interaction with age (p<0.001), being stronger in younger age groups (under 45 years HR: 17.9 and 16.6 respectively for English, Danish) than in patients over 75 years (HR 2.1 and 2.9 respectively). In patients with alcoholic cirrhosis, 30-day mortality following a hip fracture was 11.1% in England and 10.0% in Denmark, giving age-adjusted post-fracture mortality rate ratios of 2.8(95% CI 1.9-3.9) and 2.0(95% CI 1.5-2.7), respectively. Conclusions: Patients with alcoholic cirrhosis have a markedly increased risk of hip fracture and post-hip fracture mortality compared with the general population.